2007
DOI: 10.1002/polb.21170
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and inhomogeneous nanostructures of dicyandiamide‐cured epoxy resins

Abstract: Dicyandiamide (DICY)-cured epoxy resins are important materials for structural adhesives and matrix resins for fiber reinforced prepregs. The objective of this study was to examine the mechanical and physical properties as well as the gel structures of the cured resins and discuss the relationships among them. Diglycidyl ether of bisphenol-A (DGEBA) oligomers were chosen as the common chemical structure of the epoxy resins. Four kinds of resin mixtures were formulated using the seven types of DGEBA oligomers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 18 publications
8
52
0
Order By: Relevance
“…25,26 Indeed it has recently been shown that the bulk toughness, solvent resistance, T g , compressive strain to failure and ductility of formation improve when narrow molecular weight distributions are maintained during the cure of epoxydicyanodiamide resins. 27 Nonetheless, the presence and origin of such internal nanostructure has remained a point of active debate in the literature. For example, early evidence for highly cross-linked 'nodule' features was predominately obtained using electron microscopy, where internal structures were exposed by fracturing.…”
Section: Insights Into Epoxy Network Nanostructural Heterogeneity Usimentioning
confidence: 99%
“…25,26 Indeed it has recently been shown that the bulk toughness, solvent resistance, T g , compressive strain to failure and ductility of formation improve when narrow molecular weight distributions are maintained during the cure of epoxydicyanodiamide resins. 27 Nonetheless, the presence and origin of such internal nanostructure has remained a point of active debate in the literature. For example, early evidence for highly cross-linked 'nodule' features was predominately obtained using electron microscopy, where internal structures were exposed by fracturing.…”
Section: Insights Into Epoxy Network Nanostructural Heterogeneity Usimentioning
confidence: 99%
“…[27][28][29][30] The fracture surfaces generally appear to have a nodular topography. From AFM measurements, [27][28][29][30] the average height of each nodule (the root mean square distance) appears to vary largely between 5 and 200 nm and may be considered a characteristic length that interacts on either side of a fractured surface. When fractured surfaces come in contact during healing, the peaks and valleys will most likely not match perfectly at the nanoscopic scale, and this will limit contact and bonding.…”
Section: Resultsmentioning
confidence: 99%
“…Sahagun and Morgan showed via atomic force microscopy (AFM) that epoxy‐amine thermosets exhibit detectable heterogeneous microstructures on the 50‐nm scale . Earlier studies supported these observations via electron microscopy of various epoxy‐amine polymers and other thermosets; however, dissenting authors argued that the electron beam was responsible for these heterogeneous surfaces through surface etching . Sahagun observed that in the absence of etched surfaces via AFM, heterogeneous nanostructures were present within crosslinked epoxy‐amine polymers.…”
Section: Introductionmentioning
confidence: 99%